PENGARUH TINGKAT PENDIDIKAN DAN PERILAKU KEUANGAN TERHADAP KINERJA KEUANGAN UMKM DI KOTA MATARAM - mutia, Galuh Ratna (Jurnal PenKoMi : Kajian Pendidikan dan Ekonomi, 2024)
This study aims to examine the effect of education level and financial behavior on the financial performance of MSMEs in Mataram City. The approach used is qualitative method with multiple regression analysis method. Sample selection in this method uses purposive sampling. The number of samples used is 30 MSMEs located in Mataram City. The results of this study show that the level of education does not have a significant influence on the financial performance of MSMEs. Meanwhile, financial behavior has a significant effect on the financial performance of MSMEs